Pemberdayaan Masyarakat melalui Edukasi Arsitektur Kearifan Lokal: Pengabdian - Baharuddin, Faizal; Ahmad Riza; Putri Ramadhan Noor; Fhadly Ilham (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Community empowerment through education on local wisdom architecture was carried out at Taman Salma Shofa Samarinda to provide new students and the community of Taman Salma Shofa in Sungai Pinang Rt.17 Samarinda with an understanding of the importance of architecture based on local wisdom and to foster students' awareness of the preservation of local culture through an architectural approach. The methods used in this activity were participatory and interactive, with material on Local Wisdom Architecture covering philosophy, function, and its application in a modern context. Participants gained knowledge and understanding of the importance of preserving cultural diversity in the context of architecture. The results of this activity showed an increase in participants' knowledge of local wisdom architecture that can be applied in the modern era and fostered collective awareness of the importance of cultural preservation in development. This activity is expected to inspire the use of local wisdom values in contemporary architectural design.